The Determinants of Indonesian Paper Export to the ASEAN Market with the Gravity Model Approach - Yudhi Zuriah Wirya Purba; Faizal Daud; Johan Tampubolon (International Journal of Innovation in Marketing Elements)
The study aimed to analyze the determinant variables that affect the value of Indonesian paper exports (HS. 4802) to the export destination countries in the ASEAN market. The study used secondary data in the form of panel data. The data were the values of Indonesian paper exports, real GDP, export price, economic distance, real exchange rate, and population growth in the ASEAN Market from 2010 to 2019. The analytical method used was panel data regression analysis with a gravity model approach. The study results show that all independent variables significantly affect the value of Indonesia's paper exports by 95%. The increase in real GDP, real exchange rate, and population growth positively affect the export value of Indonesian paper products, with the coefficient of elasticity of each being 4.24, 0.40, and 0.70, respectively. Conversely, the increase in export price and economic distance harms the export value of Indonesian paper products, with the coefficient of elasticity of each being -5.61 and -2.74, respectively.